Pengembangan Kapasitas Pemerintah Dalam Kebijakan Pendidikan: Sebuah Alternatif Untuk Mengoptimalkan Cetak Biru Pendidikan Malaysia 2013-2025 (Sekolah) Melalui Pendekatan Kolaboratif Di Kampung Mukim Singkir Kedah Malaysia - Fikri, Rijalul; Amrillah, M Faisal; Mulianto, Budi; Mohammad, Nur'Jila binti; Gusnaldi, Ryan (BERDAYA : Jurnal Pengabdian Kepada Masyarakat, 2023)
This community service is a collaborative approach to strengthen the implementation of the Malaysian Education Blueprint 2013-2025 (Sekolah) by focusing on building government capacity in education policy. By involving various stakeholders, such as government agencies, educational institutions, communities, and civil society organizations, this approach aims to improve the quality and accessibility of education in Malaysia. we use knowledge sharing platforms to equip government officials with the necessary skills and knowledge in education policy with a collaborative approach through ICT. Creating an enabling environment that encourages continuous learning and innovation is critical. By prioritizing government capacity building and encouraging collaboration, Malaysia can effectively implement its education blueprint and make significant progress in providing quality education for the whole society. This community service was carried out in Kampung Mukim Singkir Yan Kedah, Malaysia.